A randomised vaccine field trial in Kenya demonstrates protection against wildebeest-associated malignant catarrhal fever in cattle - Cook, Elizabeth A.J.; Russell, George; Grant, Dawn; Mutisya, Christine N.; Omoto, Lazarus; Dobson, Elizabeth; Lankester, Felix; Nene, Vishvanath M. (Elsevier, 2019)
Wildebeest-associated malignant catarrhal fever (WA-MCF), a fatal disease of cattle caused by alcelaphine herpesvirus 1 (AlHV-1), is one of the most important seasonal diseases of cattle in wildebeest endemic areas, with annual incidence reaching 10%. Here we report efficacy of over 80% for a vaccine based on the attenuated AlHV-1 C500 strain, in preventing fatal WA-MCF in cattle exposed to natural wildebeest challenge. The study was conducted at Kapiti Plains Ranch Ltd, south-east of Nairobi, Kenya. In 2016, 146 cattle were selected for a randomised placebo-controlled trial. Cattle were stratified according to breed and age and randomly assigned to groups given vaccine or culture medium mixed with Emulsigen®. Cattle received prime and boost inoculations one month apart and few adverse reactions (n = 4) were observed. Indirect ELISA demonstrated that all cattle in the vaccine group developed a serological response to AlHV-1. The study herd was grazed with wildebeest from one month after booster vaccination. Three cattle, two that received vaccine and one control, succumbed to conditions unrelated to WA-MCF before the study ended. Twenty-five cattle succumbed to WA-MCF; four of the remaining 71 cattle in the vaccine group (5.6%) and 21 of the remaining 72 control cattle (29.2%; χ2 = 13.6, df = 1, p < 0.001). All of the WA-MCF affected cattle were confirmed by PCR to be infected with AlHV-1 and in 23 cases exhibited histopathology typical of WA-MCF. Vaccine efficacy was determined to be 80.6% (95% CI 46.5–93.0%). Hence, the AlHV-1 C500 vaccine is a safe and potentially effective novel method for controlling WA-MCF in cattle. The implementation of this vaccine may have significant impacts on marginalised cattle keeping communities.